2018
DOI: 10.1021/acs.analchem.8b00013
|View full text |Cite
|
Sign up to set email alerts
|

Laser Cleavable Probes-Based Cell Surface Engineering for in Situ Sialoglycoconjugates Profiling by Laser Desorption/Ionization Mass Spectrometry

Abstract: Cell-surface sialoglycoconjugates (sialoglycoproteins and sialoglycolipids) play important roles in cell-cell interactions and related tumor metastasis process. Although there have been some analytical methods to evaluate the sialoglycoconjugates, an effective method providing both qualitative and quantitative information is still deficient. Here we establish an extraction-free, sensitive, and high-throughput platform to realize in situ detection of the cell-surface sialoglycoconjugates on various cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For the first one, several groups developed different ways to enhance the homogeneity of the target surface. 518 For example, Thomas et al reported that desorption/ionization on silicon (DIOS) allows for the analysis of related small molecules in the absence of matrix with a good reproducibility. 9 Nie et al used carbon nanodots (CDs) with excellent water solubility as the matrix for quantified MALDI-TOF MS analysis of glucose in serum.…”
Section: Introductionmentioning
confidence: 99%
“…For the first one, several groups developed different ways to enhance the homogeneity of the target surface. 518 For example, Thomas et al reported that desorption/ionization on silicon (DIOS) allows for the analysis of related small molecules in the absence of matrix with a good reproducibility. 9 Nie et al used carbon nanodots (CDs) with excellent water solubility as the matrix for quantified MALDI-TOF MS analysis of glucose in serum.…”
Section: Introductionmentioning
confidence: 99%
“…22 They can be also directly observed in mass spectrometers where their lifetime is increased in vacuum and the concentration of nucleophiles is low. 23 Carbocations are strong electrophiles that should react with the nucleophilic residues in proteins. There is only one reported footprinter based on a carbocation, that is, the Koshland's reagent that labels W via an S N 1 reaction.…”
mentioning
confidence: 99%
“…35−37 For example, the cell surface proteins labeled by trityl sulfane probes have been successfully detected in situ by MSIAs. 36 More small molecules with MS sensitivity and extensible structures, including polyethylene glycols, 31 quaternary ammonium compounds, 34 and rhodamine derivatives, 37 are usually served as mass tags. We previously developed the rhodamine-based mass tags (RMTs) that achieved 10 7 -fold signal amplification 34 and have been applied to the in situ detection of proteins on cell surfaces at a single-cell level by mass cytometry.…”
mentioning
confidence: 99%
“…However, the intact protein detection is always challenging with ESI-MS because they suffer from low ionization efficiency even without salt interference, let alone the in situ detection. An alternative to achieve high sensitivity and in situ detection of proteins is the mass spectrometry-based immunoassay (MSIA), which alters the detection of protein to that of labeled mass tags with high ionization efficiency. , Benefitting from signal amplification of mass tags, MSAIs enable the highly sensitive protein detection with detection limits of attomole to zeptomole. , Furthermore, the MSIAs dispense with the protein isolation or extraction, and proteins on cell surfaces can be analyzed in situ. For example, the cell surface proteins labeled by trityl sulfane probes have been successfully detected in situ by MSIAs .…”
mentioning
confidence: 99%
See 1 more Smart Citation